Greywaren - Stiefvater, Maggie, 1981- (Stiefvater, Maggie, 1981- Dreamer trilogy, 2022)
Niall and Mór escaped their homeland for a new start, and lost themselves in what they found. Declan has grown up as the responsible son, the responsible brother--only to find there is no way for him to keep his family safe. Ronan has always lived on the edge between dreams and waking... but now that edge is gone, and he is falling. Matthew has been the happy child, the brightest beam. But rebellion beckons, because it all feels like an illusion now. This world was not made for such a family--a family with the power to make a world and break it. If they cannot save each other or themselves, we are all doomed.